The Self-perception Debate: Do social media and platforms need better regulation? - Chang Ranshiqi (SHS Web of Conferences, 2024)
With the increasing development of social media in today’s society, the development of new media is also accompanied by the impact on self-identity and the spread of false information on the network, which makes user cognition more easily misled and leads to over-dependence. Based on the “cognitive dissonance theory”, “existence theory” and from the perspective of users and the background of the current use of social media, this paper analyzes the impact of social media on self-identity, the spread of rumors and false information, and excessive dependence, and finally discusses its regulation measures.